Analysis of The Effect of Accounting Education, Motivation And Availability of Job Information on Accounting Students' Interest In A Career As An Accountant - Yolanda, Nabila; Izzati, Dina; Zahrani, Vista; Parsi, Citra; Miranda, Aqilah; Arnita, Vina (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2025)
This study aims to analyze the effect of accounting education, motivation, and the availability of job information on accounting students' interest in a career as an accountant. The phenomenon of shifting student interest in choosing a career outside accounting may threaten the availability of professional accountants in the future. Using a quantitative approach and a systematic survey design, data were collected from 100 students of accounting study programs in Medan who had taken the "Basic Accounting" course. The analysis results show that accounting education has a significant influence on student interest (T-statistic 2.927, P-Value 0.002), followed by learning motivation (T-statistic 4.214, P-Value 0.000) and availability of job information (T-statistic 2.715, P-Value 0.043). The R² value of 0.757 indicates that the three variables explain 75% of the variation in students' interest in a career as an accountant. These findings emphasize the importance of improving the quality of accounting education, strong motivation among students, and adequate access to job information. Recommendations are given for universities to design more relevant and informative educational programs to increase students' interest in the accounting profession in a sustainable manner.